Study on Prescribing Patterns of Antimicrobial Agents In Liver Disease Patients: Pharmaceutical Science-Pharmacy practice for good health Promotion - K.Bharathi Priya; Dr.K.N.Chandan Kumar; Adarsh Raj; Christy Sara Saji; Rebekah John (International Journal of Life Science and Pharma Research, 2022)
The present study aims at analyzing the prescribing patterns of antimicrobial agents in different liver diseases and to identify the drug-drug interactions among the prescribed drugs. A cross sectional observational study was conducted from February to July 2018. A total of 120 cases of patients receiving antimicrobials having different types of liver diseases were included. Statistical analysis shows that 80% of the popuation were male and 64% of the population was above the age of 50 years. . Liver disease like Liver Cirrhosis, Non alcoholic steato hepatitis, Viral hepatits, Jaundice, Hepatocellular carcinoma was found to be present among the study population, 50% of the population was overweight and 32% were alcoholic. Majority of them had ascites, abdominal distention and pedal edema as chief complaints and complications were hepatic encephalopathy and esophageal varices. The prescribed antimicrobial agents were antibiotics (95%) viz., Piptaz, rifaximin and taxim. antivirals (4%) such as entecavir and antifungals (1%) likeflucanazole. The drugs were prescribed according to the guidelines of the hospital. Mostly broad spectrum antibiotics were used in the management of liver disorders like Linezolid, Meropenem, Ertapenem, and Tobramycin. In severe cases combination of antimicrobials were given for effective therapy. Patient’s transplantation was based on the MELD score, as the MELD score increases, the mortality rate also increases. MELD score =40 indicates mortality rate is >70%.